Paint for magnesium alloy material and preparation method thereof

By using composite base materials in paint, including film forming base materials, corrosion-inhibiting capsules and chitosan modified nanoparticles, the problem of the prone to bubbles after the application of paint on the surface of magnesium alloy is solved, and the anticorrosion performance and service life of magnesium alloy is significantly improved.

CN119614044AInactive Publication Date: 2025-03-14ROYALBABY CYCLE TIANJIN CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411877097.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

After the existing paint is applied on the surface of magnesium alloy, it is easy to produce bubbles in harsh environments, resulting in a decrease in the anti-corrosion performance of the coating and damage the service life of the magnesium alloy.

Method used

Compound base materials, including film forming base materials, corrosion-inhibiting capsules and chitosan modified nanoparticles, are used to improve the stability and corrosion resistance of the paint through the synergistic effect of these substances.

Benefits of technology

The formation of a dense and firm coating significantly improves the corrosion resistance and service life of magnesium alloys.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005197200840000061
    Figure BDA0005197200840000061
  • Figure BDA0005197200840000071
    Figure BDA0005197200840000071
  • Figure BDA0005197200840000081
    Figure BDA0005197200840000081
Patent Text Reader

Abstract

The invention relates to the field of curing coatings, and particularly discloses paint for a magnesium alloy material and a preparation method of the paint. The invention discloses paint for a magnesium alloy material. The paint comprises the following raw materials in parts by weight: 42-45 parts of a compound base material; 19-20 parts of a curing agent; 7-8 parts of a pigment; 4-5 parts of an auxiliary agent; the compound base material is prepared from a film-forming base material, a corrosion inhibition capsule and chitosan modified nanoparticles according to the weight ratio of 40 to (1.5 to 2.5) to (0.32 to 0.48); the preparation method comprises the following steps: mixing the film-forming base material, the corrosion inhibition capsule and the chitosan modified nanoparticles to obtain a compound base material, then adding the pigment and the auxiliary agent, uniformly stirring, then adding the curing agent, and stirring to obtain the paint for the magnesium alloy material. After the product is sprayed and cured, a coating can be formed on the surface of a magnesium alloy material, and the coating has the advantages of being excellent in corrosion resistance, not prone to cracking and high in internal uniformity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of curing coatings, and in particular to a paint for magnesium alloy materials and a preparation method thereof. Background Art

[0002] At present, in the field of metal corrosion protection, paint is widely used as a common protective coating raw material on the surface of various metal materials. Its main components include film-forming base material, curing agent, additives (anti-settling agent, leveling agent, etc.), solvent and pigment. Magnesium alloy is widely used in aerospace, automotive industry and other fields due to its low density, high strength and corrosion resistance. Therefore, paint for magnesium alloy material has emerged and has been continuously and steadily developed. However, with actual use, people have found that the existing paint has encountered some difficulties in the application process of magnesium alloy surface, that is, the coating formed by this paint is prone to bubbles in harsh environment, resulting in the decline of the anti-corrosion performance of the coating itself, which seriously damages the service life of magnesium alloy.

[0003] The existing solution is to improve the performance of paint by improving the paint formula, such as adding silicone resin modifiers to improve the heat resistance and weather resistance of paint. However, although these measures help improve the performance of paint on magnesium alloys, the cost of the improved paint is high, which is not conducive to large-scale promotion and application. The most important thing is that even if certain additives are added, the paint may still crack or even fall off after long-term exposure to harsh environments. Therefore, how to improve the stability of paint used for magnesium alloys has become a top priority. Summary of the invention

[0004] In order to solve the above technical problems, the present application provides a paint for magnesium alloy material and a preparation method thereof.

[0005] In the first aspect, the present application provides a paint for magnesium alloy materials, the raw materials used include the following components in parts by weight: 42-45 parts of a compound base material; 19-20 parts of a curing agent; 7-8 parts of a pigment; and 4-5 parts of an additive; the compound base material includes a film-forming base material, corrosion-inhibiting capsules, and chitosan modified nanoparticles in a weight ratio of 40:(1.5-2.5):(0.32-0.48).

[0006] By adopting the above-mentioned technical scheme, the present application obtains a composite base material after mixing a film-forming base material, corrosion-inhibiting capsules and chitosan-modified nanoparticles, wherein the chitosan-modified nanoparticles can reduce the spatial structural porosity in the system and improve the corrosion diffusion resistance. The nanoparticles therein have a large specific surface area. In addition, the present application uses chitosan to modify them, which significantly improves the dispersibility of the nanoparticles in the system and improves the uniformity and leveling of the overall medium. The corrosion-inhibiting capsules can form a passivation layer and a protective layer on the surface of the magnesium alloy. When the coating is not damaged, the corrosion-inhibiting capsules can maintain their own complete shape. Once the coating is broken, the environmental pH value around the corrosion-inhibiting capsules changes and the corrosion-inhibiting substances will be released immediately, thereby forming a strong protection for the surface of the magnesium alloy.

[0007] The paint of the present application can form a dense and firm coating on the surface of the magnesium alloy after curing. The various substances in the paint play a synergistic role and jointly improve the stability of the paint, thereby significantly improving the anti-corrosion ability of the coating and greatly extending the service life of the magnesium alloy.

[0008] The film-forming base material of the present application takes bisphenol A epoxy resin E-51 as an example, the curing agent takes a polyamine curing agent as an example, the pigment takes phthalocyanine blue as an example, and the auxiliary agents include a leveling agent, a stabilizer and an anti-settling agent. The above substances can be routinely adjusted by those skilled in the art according to actual conditions. The present application only uses the above parameters and substances as examples for illustration, and does not limit the protection scope of the present application accordingly.

[0009] Preferably, the weight ratio of the film-forming base material, the corrosion-inhibiting capsules and the chitosan-modified nanoparticles is 40:2:0.4.

[0010] By adopting the above technical scheme, the present application strictly controls the weight ratio of the film-forming base material, the corrosion-inhibiting capsules and the chitosan-modified nanoparticles. If the added amount of the corrosion-inhibiting capsules and the chitosan-modified nanoparticles is too small, they cannot play an effective protective role; if the added amount of the corrosion-inhibiting capsules and the chitosan-modified nanoparticles is too large, the adhesion of the paint to the magnesium alloy and the dispersion effect inside the coating will be reduced, which will in turn damage the anti-corrosion ability of the coating and shorten the service life of the magnesium alloy.

[0011] Preferably, the main raw material of the core material of the corrosion-inhibiting capsule includes benzotriazole, and the main raw material of the wall material includes polyaniline.

[0012] By adopting the above technical scheme, the present application uses benzotriazole as the core material and polyaniline as the wall material to obtain a corrosion-inhibiting capsule with corrosion inhibition ability. Polyaniline will undergo a reversible redox conversion in the system to form a passivation layer on the surface of the magnesium alloy. If the coating is affected by an excessively harsh external environment, causing the coating to rupture and produce microcracks, corrosive media such as water and oxygen will successively enter the coating, attacking the magnesium alloy matrix to corrode it and produce a large amount of metal ions. At this time, benzotriazole is released due to the rupture of the wall material, and will quickly complex with the metal ions on the surface of the magnesium alloy to form a protective layer, thereby slowing down or even preventing the corrosion of the metal.

[0013] Preferably, the method for preparing the corrosion-inhibiting capsules comprises the following steps: I. Dispersing hollow mesoporous microspheres and benzotriazole in a weight ratio of 10:(8-12) in an organic solvent, ultrasonically treating, standing, filtering, washing, and drying to obtain an intermediate product; II. Disperse the intermediate product, aniline, cobalt sulfate heptahydrate and ammonium persulfate in a weight ratio of 10:(4.5-5.0):0.8:14 in hydrochloric acid, stir to react, filter, wash and freeze-dry to obtain corrosion-inhibiting capsules.

[0014] By adopting the above technical solution, the present application utilizes hollow mesoporous microspheres as micro-nano containers, which cooperate with polyaniline to achieve a good controlled release regulating effect on benzotriazole, and releases benzotriazole for complexation reaction only during the critical period of coating rupture, thereby achieving the effect of accurately and timely protecting the magnesium alloy.

[0015] Preferably, in step I, the weight ratio of the hollow mesoporous microspheres to benzotriazole is 10:10.

[0016] By adopting the above technical solution, the present application strictly controls the weight ratio of hollow mesoporous microspheres to benzotriazole, ensuring that the loading rate of benzotriazole in the hollow mesoporous microspheres reaches the highest possible level without incurring additional costs, thereby improving the corrosion inhibition ability of the corrosion inhibition capsules.

[0017] Preferably, in step II, the weight ratio of the intermediate product, aniline, cobalt sulfate heptahydrate and ammonium persulfate is 10:4.6:0.8:14.

[0018] By adopting the above technical scheme, the present application strictly controls the weight ratio of the intermediate product, aniline, cobalt sulfate heptahydrate and ammonium persulfate, so that the core-to-wall ratio of the finally obtained corrosion-inhibiting capsules is at the most suitable level. Experimental data show that at this time, the corrosion inhibition effect of the corrosion-inhibiting capsules is optimal, and the speed of compensating for coating rupture is also very fast. At the same time, it can also improve the integrity of the coating as much as possible, thereby improving the service life of the magnesium alloy.

[0019] Preferably, the nanoparticles of the chitosan modified nanoparticles are graphite carbon nitride.

[0020] Preferably, the preparation method of the chitosan modified nanoparticles comprises the following steps: dispersing chitosan and graphite carbon nitride in a weight ratio of (18-20):1 in water, dialyzing for 2-3 days, then centrifuging to obtain a lower precipitate, washing, and freeze-drying to obtain chitosan modified nanoparticles.

[0021] By adopting the above-mentioned technical scheme, the present application adopts graphite carbon nitride as nanoparticles. Compared with nanoparticles such as nano-silicon dioxide and graphene, it has richer residual functional groups and is more tightly bound to chitosan, thereby obtaining higher epoxy resin compatibility and being able to obtain a more sufficient dispersion effect in the system. At the same time, graphite carbon nitride has a unique layered structure. Adding it to the system can make the density and leveling of the coating higher, thereby improving the corrosion resistance of the coating.

[0022] In the second aspect, the present application provides a method for preparing paint for magnesium alloy materials, comprising the following steps: mixing a film-forming base material, corrosion-inhibiting capsules and chitosan-modified nanoparticles to obtain a composite base material, then adding pigments and additives, stirring evenly, adding a curing agent, stirring, and obtaining paint for magnesium alloy materials.

[0023] By adopting the above technical scheme, the present application first mixes the film-forming base material, corrosion-inhibiting capsules and chitosan-modified nanoparticles to obtain a composite base material, then adds pigments and additives while the composite base material is mixed, mixes it a second time, then adds a curing agent, mixes it a third time, and finally obtains a paint for magnesium alloy materials. The paint has high internal dispersion and good fluidity, is very suitable for anti-corrosion protection treatment of the surface of magnesium alloy, and has high use value.

[0024] In a third aspect, the present application provides an application of a paint for magnesium alloy material, comprising the following steps: spraying and curing the above-mentioned paint for magnesium alloy material to obtain a coating.

[0025] By adopting the above-mentioned technical scheme, the present application sprays and cures the mixed paint on the surface of the magnesium alloy to form a dense and uniform coating, which not only can beautify the appearance, but also can significantly improve the corrosion resistance, weather resistance and service life of the magnesium alloy.

[0026] In summary, this application has the following beneficial technical effects: 1. The paint of the present application can form a dense and firm coating on the surface of the magnesium alloy after curing. The various substances in the paint play a synergistic role and jointly improve the stability of the paint, thereby significantly improving the anti-corrosion ability of the coating and greatly extending the service life of the magnesium alloy; 2. The present application first mixes a film-forming base material, corrosion-inhibiting capsules and chitosan-modified nanoparticles to obtain a composite base material, then adds pigments and additives while the composite base material is mixed, mixes twice, then adds a curing agent, mixes three times, and finally obtains a paint for magnesium alloy material. The paint has high internal dispersion and good fluidity, is very suitable for anti-corrosion protection treatment of magnesium alloy surface, and has high use value; 3. In the present application, the mixed paint is sprayed on the surface of the magnesium alloy and cured to form a dense and uniform coating, which not only improves the appearance, but also significantly improves the corrosion resistance, weather resistance and service life of the magnesium alloy. DETAILED DESCRIPTION

[0027] Material Source Unless otherwise specified, the raw materials used in this application are all commercially available products, specifically: Hollow mesoporous microspheres were purchased from Hangzhou Jikang New Materials Co., Ltd. with a specific surface area of ​​500 m 2 / g, inner diameter 350nm; Benzotriazole was purchased from Aladdin Reagent Co., Ltd.; Aniline was purchased from Aladdin Reagent Co., Ltd.; Cobalt sulfate heptahydrate was purchased from Aladdin Reagent Co., Ltd.; Ammonium persulfate was purchased from MacLean Reagent Co., Ltd.; Chitosan was purchased from Sigma-Aldrich; Graphitic carbon nitride was purchased from Guangdong Wengjiang Chemical Reagent Co., Ltd., CAS No. 143334-20-7; Bisphenol A epoxy resin E-51 was purchased from MacLean Reagent Co., Ltd.; Phthalocyanine blue was purchased from BASF Chemical Technology; The leveling agent was purchased from Laiyang Shengbang Organic Silicone Technology Co., Ltd., organic silicon leveling agent, model SI-X101 The stabilizer was purchased from Jinan Chaoyixing Chemical Co., Ltd., and its main component was methyltin mercaptan; The anti-settling agent was purchased from Shanghai Tongshi Technology Co., Ltd., model number PA-103; The curing agent was purchased from Shandong Aite Chemical Co., Ltd., and its main component was polyethylene polyamine; The magnesium alloy was purchased from Suzhou Tamuchuan Rare Metal Products Co., Ltd. with the model number of AZ31b and a melting point of 880°C.

[0028] The present application is further described in detail below in combination with preparation examples, embodiments and comparative examples.

[0029] Preparation Example 1.1 The preparation method of the corrosion-inhibiting capsule comprises the following steps: I. Disperse 100 g of hollow mesoporous microspheres uniformly in 1 L of 8 wt % benzotriazole ethanol solution, disperse the resulting solution by ultrasonication for 15 min, move it to a vacuum drying oven, let it stand at room temperature for 15 h, filter it, wash it with deionized water three times, and dry it at 50° C. for 12 h to obtain an intermediate product; II. Dissolve 45 g of aniline in 1 L of 1 mol / L hydrochloric acid solution, and stir magnetically for 12 h to obtain an aniline acid solution. Add 100 g of the intermediate product to the aniline acid solution, then dissolve 8 g of cobalt sulfate heptahydrate and 140 g of ammonium persulfate in 500 mL of 1 mol / L hydrochloric acid, and then mix with the aniline acid solution to which the intermediate product was added. Stir and react at room temperature at a speed of 200 r / min for 12 h, filter, wash, and freeze-dry for 4 h to obtain corrosion-inhibiting capsules.

[0030] Preparation Example 1.2 The preparation method of the corrosion-inhibiting capsule comprises the following steps: I. Disperse 100 g of hollow mesoporous microspheres uniformly in 1 L of 12 wt% benzotriazole ethanol solution, disperse the resulting solution by ultrasonic dispersion for 15 min, move it to a vacuum drying oven, let it stand at room temperature for 15 h, filter it, wash it with deionized water three times, and dry it at 50° C. for 12 h to obtain an intermediate product; II. Dissolve 50 g of aniline in 1 L of 1 mol / L hydrochloric acid solution, and stir magnetically for 12 h to obtain an aniline acid solution. Add 100 g of the intermediate product to the aniline acid solution, then dissolve 8 g of cobalt sulfate heptahydrate and 140 g of ammonium persulfate in 500 mL of 1 mol / L hydrochloric acid, and then mix with the aniline acid solution to which the intermediate product was added. Stir and react at room temperature at a speed of 200 r / min for 12 h, filter, wash, and freeze-dry for 4 h to obtain corrosion-inhibiting capsules.

[0031] Preparation Example 1.3 The preparation method of the corrosion-inhibiting capsule is different from that of Preparation Example 1.1 in that: in step I, the concentration of benzotriazole in the benzotriazole ethanol solution is 10 wt %, and the rest is the same as that of Preparation Example 1.1.

[0032] Preparation Example 1.4 The preparation method of the corrosion-inhibiting capsules is different from that of Preparation Example 1.3 in that in step II, the amount of aniline used is 46 g, and the rest is the same as that of Preparation Example 1.3.

[0033] Preparation Example 1.5 The preparation method of the corrosion-inhibiting capsules is different from that of Preparation Example 1.3 in that in step II, the amount of aniline used is 47 g, and the rest is the same as that of Preparation Example 1.3.

[0034] Preparation Example 1.6 The preparation method of the corrosion-inhibiting capsules is different from that of Preparation Example 1.3 in that in step II, the amount of aniline used is 48 g, and the rest is the same as that of Preparation Example 1.3.

[0035] Preparation Example 1.7 The preparation method of the corrosion-inhibiting capsules is different from that of Preparation Example 1.3 in that in step II, the amount of aniline used is 49 g, and the rest is the same as that of Preparation Example 1.3.

[0036] Preparation Example 2.1 The preparation method of chitosan modified nanoparticles comprises the following steps: 200 g of chitosan and 200 g of acetic acid were dissolved in water to obtain a mixed solution with a chitosan concentration of 2 wt%, and then 10 g of graphite carbon nitride was dispersed in ultrapure water and blended with the mixed solution, dialyzed for 2 days, and the deionized water was replaced every 4 hours. After the dialysis, the mixture was centrifuged at a speed of 10000 r / min for 15 min to remove the uncomplexed chitosan in the upper layer, and the lower layer of precipitate was obtained. Ultrapure water was added for ultrasonic washing, and the mixture was freeze-dried to obtain chitosan-modified nanoparticles.

[0037] Preparation Example 2.2 The preparation method of chitosan modified nanoparticles comprises the following steps: 180 g of chitosan and 180 g of acetic acid were dissolved in water to obtain a mixed solution with a chitosan concentration of 2 wt%, and then 10 g of graphite carbon nitride was dispersed in ultrapure water and blended with the mixed solution, dialyzed for 3 days, and the deionized water was replaced every 4 hours. After the dialysis, the mixture was centrifuged at a speed of 10000 r / min for 15 min to remove the uncomplexed chitosan in the upper layer, and the lower layer of precipitate was obtained. Ultrapure water was added for ultrasonic washing, and the mixture was freeze-dried to obtain chitosan-modified nanoparticles.

[0038] Example 1.1 A method for preparing paint for magnesium alloy material, comprising the following steps: According to the amount of each substance in Table 1, bisphenol A epoxy resin E-51, the corrosion inhibition capsules prepared in Preparation Example 1.1, and the chitosan modified nanoparticles prepared in Preparation Example 2.1 were mixed to obtain a composite base material, and then phthalocyanine blue, leveling agent, stabilizer and anti-settling agent were added. After stirring for 15 minutes, the curing agent was added and stirred again for 15 minutes to obtain a paint for magnesium alloy.

[0039] Example 1.2 A method for preparing paint for magnesium alloy material, comprising the following steps: According to the amount of each substance in Table 1, bisphenol A epoxy resin E-51, the corrosion-inhibiting capsules prepared in Preparation Example 1.2, and the chitosan modified nanoparticles prepared in Preparation Example 2.2 were mixed to obtain a composite base material, and then phthalocyanine blue, leveling agent, stabilizer and anti-settling agent were added. After stirring for 15 minutes, the curing agent was added and stirred again for 15 minutes to obtain a paint for magnesium alloy materials.

[0040] Table 1 Amount of each substance used in Examples 1.1-1.2 / g Example 1.3 A method for preparing paint for magnesium alloy material, which is different from Example 1.1 in that the amount of bisphenol A epoxy resin E-51 used is 396.24g, the amount of corrosion-inhibiting capsules prepared in Preparation Example 1.1 is 19.8g, the amount of chitosan modified nanoparticles prepared in Preparation Example 2.1 is 3.96g, and the rest is the same as Example 1.1.

[0041] Example 2.1 A method for preparing paint for magnesium alloy material, which is different from Example 1.1 in that the corrosion-inhibiting capsules prepared in Preparation Example 1.1 are replaced by the corrosion-inhibiting capsules prepared in Preparation Example 1.3, and the rest are the same as Example 1.1.

[0042] Example 2.2 A method for preparing paint for magnesium alloy material, which is different from Example 2.1 in that the corrosion-inhibiting capsules prepared in Preparation Example 1.3 are replaced by the corrosion-inhibiting capsules prepared in Preparation Example 1.4, and the rest are the same as Example 2.1.

[0043] Example 2.3 A method for preparing paint for magnesium alloy material, which is different from Example 2.1 in that the corrosion-inhibiting capsules prepared in Preparation Example 1.3 are replaced by the corrosion-inhibiting capsules prepared in Preparation Example 1.5, and the rest are the same as Example 2.1.

[0044] Example 2.4 A method for preparing paint for magnesium alloy material, which is different from Example 2.1 in that the corrosion-inhibiting capsules prepared in Preparation Example 1.3 are replaced by the corrosion-inhibiting capsules prepared in Preparation Example 1.6, and the rest are the same as Example 2.1.

[0045] Example 2.5 A method for preparing paint for magnesium alloy material, which is different from Example 2.1 in that the corrosion-inhibiting capsules prepared in Preparation Example 1.3 are replaced by the corrosion-inhibiting capsules prepared in Preparation Example 1.7, and the rest are the same as Example 2.1.

[0046] Comparative Example 1 The difference from Example 1.1 is that the amount of bisphenol A epoxy resin E-51 used is 410g, the amount of corrosion-inhibiting capsules prepared in Preparation Example 1.1 is 7.58g, the amount of chitosan modified nanoparticles prepared in Preparation Example 2.1 is 2.42g, and the rest is the same as Example 1.1.

[0047] Comparative Example 2 The difference from Example 1.1 is that the amount of bisphenol A epoxy resin E-51 used is 380g, the amount of corrosion-inhibiting capsules prepared in Preparation Example 1.1 is 37.9g, the amount of chitosan modified nanoparticles prepared in Preparation Example 2.1 is 12.1g, and the rest is the same as Example 1.1.

[0048] Performance Testing First, the magnesium alloy is cut into several pieces of magnesium alloy plates with a size of 150mm×70mm×1mm to ensure that there are no defects (pores, scratches and oxidation color) on the surface. The surface roughness Ra is detected to be 0.8±0.1um. Then the surface is cleaned and dried, and the paint obtained in the embodiment and the comparative example is poured into a special spraying machine. The paint is evenly sprayed on the surface of the magnesium alloy plate. The paint just sprayed is allowed to stand for 30 minutes to facilitate initial consolidation. The paint is put into an oven and cured for 2 hours at a preset temperature of 80°C to form a film, and the sample to be tested is obtained.

[0049] 1. Conduct salt spray resistance test on each sample to be tested according to the test method of 5.2 neutral salt spray test in GB / T 10125-2012, and record the weight loss rate of the material after 7 days in Table 2; 2. Use a scalpel to scratch a cross crack (3 cm long, 20 μm wide) on the surface of the sample to be tested, ensuring that the scratch penetrates the coating to reach the magnesium alloy substrate. Place the scratched sample in a 3.5 wt% NaCl solution at room temperature for immersion, and record the material weight loss rate (the weight loss rate is calculated based on the unimmersed material) for 1 day, 5 days, 15 days and 30 days in Table 2.

[0050] Table 2 Performance test Data Analysis: As can be seen from Table 2, the weight loss rate of Examples 1.1-1.2 after 7 days of neutral salt spray test treatment is 0.825-0.826‰, and the weight loss rate in the scratch immersion test for 1 day is 0.634-0.636%, and the weight loss rate for 30 days is only 0.652-0.654%, which proves that the chitosan modified nanoparticles of the present application can reduce the spatial structure porosity in the system, improve the corrosion diffusion resistance of the coating, and the corrosion inhibition capsules play the role of forming a passivation layer and a protective layer on the surface of the magnesium alloy. When the coating is not damaged, the corrosion inhibition capsules can maintain their own complete form. Once the coating is broken, the pH value of the environment around the corrosion inhibition capsules changes and the corrosion inhibition substances are immediately released, thereby forming a strong protection for the surface of the magnesium alloy. Multiple substances play a synergistic role and jointly improve the stability of the paint, thereby significantly improving the anti-corrosion ability of the coating and greatly extending the service life of the magnesium alloy. The weight loss rate of Example 1.3 after 7 days of neutral salt spray test treatment and the weight loss rates of 1 day, 5 days, 15 days and 30 days in the scratch immersion test are all lower than those in Example 1.1, proving that the present application further improves the anti-corrosion ability of the coating by strictly controlling the weight ratio of the film-forming base material, the corrosion-inhibiting capsules and the chitosan-modified nanoparticles; The weight loss rate after 7 days of neutral salt spray test treatment in Example 2.1, and the weight loss rates of 1 day, 5 days, 15 days and 30 days in the scratch immersion test are all lower than those in Example 1.1. At the same time, the relative change between the 1-day weight loss rate in the scratch immersion test and the weight loss rates of the last three times is also smaller than that in Example 1.1, which proves that the present application strictly controls the weight ratio of hollow mesoporous microspheres to benzotriazole, and can ensure that the loading rate of benzotriazole in the hollow mesoporous microspheres reaches the highest possible level without incurring additional costs, thereby improving the corrosion inhibition capacity of the corrosion inhibition capsules; The weight loss rate of Example 2.2 after 7 days of neutral salt spray test treatment, and the weight loss rates of 1 day, 5 days, 15 days and 30 days in the scratch immersion test are all lower than those in Example 2.1. At the same time, the relative change between the 1-day weight loss rate in the scratch immersion test and the weight loss rates of the last three times is also smaller than that in Example 2.1, which proves that the application can make the core-to-wall ratio of the corrosion-inhibiting capsule finally obtained at the most suitable level by strictly controlling the weight ratio of the intermediate product, aniline, cobalt sulfate heptahydrate and ammonium persulfate. At this time, the corrosion inhibition effect of the corrosion-inhibiting capsule is optimal, the speed of compensating for the coating rupture is also very fast, and the integrity of the coating can be improved as much as possible, thereby improving the service life of the magnesium alloy; The weight loss rate of the neutral salt spray test of comparative example 1-2 after 7 days of treatment, and the weight loss rates of 1 day, 5 days, 15 days and 30 days in the scratch immersion test are all higher than those in Example 1.1. At the same time, the relative change of the 1-day weight loss rate in the scratch immersion test and the weight loss rates of the last three times is also much greater than that in Example 1.1, which proves that the paint of the present application can form a dense and firm coating on the surface of the magnesium alloy after curing, and the various substances in the paint play a synergistic role, which jointly improves the stability of the paint, thereby significantly improving the corrosion resistance of the coating and greatly extending the service life of the magnesium alloy. In addition, the present application can further improve the corrosion resistance of the coating by controlling the weight ratio of the film-forming base material, the corrosion-inhibiting capsules and the chitosan-modified nanoparticles. If the amount of the corrosion-inhibiting capsules and the chitosan-modified nanoparticles added is too small, they cannot play an effective protective role; if the amount of the corrosion-inhibiting capsules and the chitosan-modified nanoparticles added is too large, the adhesion of the paint to the magnesium alloy and the dispersion effect inside the coating will be reduced, which will damage the corrosion resistance of the coating and shorten the service life of the magnesium alloy.

[0051] The embodiments of this specific implementation method are all preferred embodiments of the present application, and are not intended to limit the protection scope of the present application. Therefore, all equivalent changes made based on the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A paint for magnesium alloy material, characterized in that: The raw materials used include the following components in parts by weight: 42-45 parts of compound base material; 19-20 parts of curing agent; 7-8 parts of pigment; 4-5 parts of auxiliary agent; the composite base material comprises a film-forming base material, corrosion-inhibiting capsules and chitosan modified nanoparticles in a weight ratio of 40:(1.5-2.5):(0.32-0.48).

2. The paint for magnesium alloy material according to claim 1, characterized in that: The weight ratio of the film-forming base material, the corrosion-inhibiting capsules and the chitosan-modified nanoparticles is 40:2:0.

4.

3. The paint for magnesium alloy material according to claim 1, characterized in that: The main raw material of the core material of the corrosion-inhibiting capsule includes benzotriazole, and the main raw material of the wall material includes polyaniline.

4. The paint for magnesium alloy material according to claim 3, characterized in that: The preparation method of the corrosion-inhibiting capsule comprises the following steps: The hollow mesoporous microspheres and benzotriazole in a weight ratio of 10:(8-12) are dispersed in an organic solvent, and after ultrasonic treatment, the mixture is allowed to stand, filtered, washed, and dried to obtain an intermediate product. The intermediate product, aniline, cobalt sulfate heptahydrate and ammonium persulfate in a weight ratio of 10: (4.5-5.0): 0.8: 14 are dispersed in hydrochloric acid, stirred for reaction, filtered, washed and freeze-dried to obtain corrosion-inhibiting capsules.

5. The paint for magnesium alloy material according to claim 4, characterized in that: In the step I, the weight ratio of the hollow mesoporous microspheres to benzotriazole is 10:

10.

6. The paint for magnesium alloy material according to claim 5, characterized in that: In the step II, the weight ratio of the intermediate product, aniline, cobalt sulfate heptahydrate and ammonium persulfate is 10:4.6:0.8:

14.

7. The paint for magnesium alloy material according to claim 1, characterized in that: The nanoparticles of the chitosan modified nanoparticles are graphite carbon nitride.

8. The paint for magnesium alloy material according to claim 7, characterized in that: The method for preparing the chitosan modified nanoparticles comprises the following steps: Chitosan and graphite carbon nitride in a weight ratio of (18-20):1 are dispersed in water, dialyzed for 2-3 days, and then centrifuged to obtain a lower precipitate, washed, and freeze-dried to obtain chitosan modified nanoparticles.

9. A method for preparing a paint for magnesium alloy material according to any one of claims 1 to 8, characterized in that: The following steps are involved: The film-forming base material, the corrosion-inhibiting capsules and the chitosan-modified nanoparticles are mixed to obtain a composite base material, and then the pigment and the auxiliary agent are added. After stirring evenly, a curing agent is added and stirred to obtain a paint for magnesium alloy materials.

10. An application of paint for magnesium alloy material, characterized in that: The method comprises the following steps: spraying the paint for magnesium alloy material according to any one of claims 1 to 8, and curing the paint to obtain a coating.

Citation Information

Patent Citations

  • Preparation and application method of acid-resistant composite material based on chitosan and graphite-phase carbon nitride

    CN116803482A